2013
DOI: 10.1186/1471-2334-13-391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of measles antibodies among health care workers in Catalonia (Spain) in the elimination era

Abstract: BackgroundInterruption of measles transmission was achieved in Catalonia (Spain) in 2000. Six years later, a measles outbreak occurred between August 2006 and June 2007 with 381 cases, 11 of whom were health care workers (HCW).The objective was to estimate susceptibility to measles in HCW and related demographic and occupational characteristics.MethodsA measles seroprevalence study was carried out in 639 HCW from six public tertiary hospitals and five primary healthcare areas. Antibodies were tested using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
2
9
0
7
Order By: Relevance
“…In our study we found that cases in HCP were mostly (55.8%) in the 25-34 y age group in concordance with the fore mentioned susceptibility study. 20 These findings are similar to those of Botelho-Nevers et al 1 suggesting that, in younger subjects, vaccination coverage remained low. Therefore, even if the prevalence of non-immune HCP seems to be low, the low uptake of MMR immunization and the appearance of measles outbreaks increase the risk of nosocomial transmission as seen in the rising trend observed in large outbreaks occurred in Catalonia during the study period.…”
Section: Discussionsupporting
confidence: 88%
“…In our study we found that cases in HCP were mostly (55.8%) in the 25-34 y age group in concordance with the fore mentioned susceptibility study. 20 These findings are similar to those of Botelho-Nevers et al 1 suggesting that, in younger subjects, vaccination coverage remained low. Therefore, even if the prevalence of non-immune HCP seems to be low, the low uptake of MMR immunization and the appearance of measles outbreaks increase the risk of nosocomial transmission as seen in the rising trend observed in large outbreaks occurred in Catalonia during the study period.…”
Section: Discussionsupporting
confidence: 88%
“…This illustrates the fact that in the era of low incidence of the disease, a high risk of nosocomial spread exists due to a lesser experience of health care workers with the disease. While infected, health care workers may be subsequently the source of spreading measles to susceptible individuals both within health care facilities and within the general population [1418]. For this reason it is necessary to ensure sufficient education of health care workers in matters of epidemiology, transmission, clinical manifestations and measles prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In response, this time has been changed later to be at 12 months. [22][23][24] In the current study, only one participant showed a seronegative response, despite being vaccinated. When interviewed, he stated that he only received one dose of the vaccine and forgot the second one.…”
Section: Discussionmentioning
confidence: 50%
“…Vaccine-related ones include inadequate attenuation, wrong route or interrupted schedule and interruption of cold chain. [21][22][23][24] In Egypt, measles vaccine was introduced as a compulsory vaccine to children at the age of 9 months, in which the vaccine might interfere with maternal Abs. In response, this time has been changed later to be at 12 months.…”
Section: Discussionmentioning
confidence: 99%